Optimization and Exploration of Office Space Design in the Post-epidemic Era - Wu Congsu (Asian Social Work Journal, 2023)
As an infectious disease that may accompany the future life of mankind for a long time, COVID19 has gradually changed people's working environment, forcing us to accelerate and deeply consider adopting a different and more flexible model to achieve sustainable work and life. This article explores the future office space model under the background of the post-epidemic era, integrates the environmental elements of office space in the current post-epidemic era from the perspective of professional practitioners, analyzes the background of the era, and research purposes, and sorts out relevant theories and materials related to office space, cases and questionnaire surveys are used as theoretical basis support. From the perspective of interior design, discuss the two aspects of people and space in the office, construct the relationship between the two, and clarify the importance of the relationship between people and the space environment in the office scene, and the necessity of physiological function and psychological construction in the work, and explore how to propose strategies for the optimization of office space design in the post-epidemic era. Strive to realize the most possible practicality and innovation of the future office space model.